2019
DOI: 10.1097/md.0000000000014317
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral percutaneous vertebroplasty for osteoporotic vertebral compression fractures in elderly patients

Abstract: Objective: To contrast the effects and complications in unilateral and bilateral percutaneous vertebroplasty (PVP) for osteoporotic vertebral compression fractures in elderly patients. Methods: Multiple databases were adopted to search relevant studies, and the articles eventually satisfied the criteria were included. All the meta-analyses were conducted with the Review Manager 5.2. To estimate the quality of each article, risk of bias table was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…However, this classification method was mostly applicable for unilateral puncture cases, because bilateral puncture injection of bone cement can often achieve a uniform distribution on both sides of the vertebral body, effectively avoiding the uneven stress caused by asymmetric distribution on the coronal plane. Many previous literatures have also confirmed that bilateral puncture does not significantly increase the risk of complications such as cement leakage and nerve injury as long as the puncture route is strictly followed [9,10]. Therefore, studying the distribution of bone cement in the sagittal plane on lateral radiographs may be more meaningful for the analysis of surgical efficacy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, this classification method was mostly applicable for unilateral puncture cases, because bilateral puncture injection of bone cement can often achieve a uniform distribution on both sides of the vertebral body, effectively avoiding the uneven stress caused by asymmetric distribution on the coronal plane. Many previous literatures have also confirmed that bilateral puncture does not significantly increase the risk of complications such as cement leakage and nerve injury as long as the puncture route is strictly followed [9,10]. Therefore, studying the distribution of bone cement in the sagittal plane on lateral radiographs may be more meaningful for the analysis of surgical efficacy.…”
Section: Discussionmentioning
confidence: 92%
“…There were 26 males and 111 females, with an average age of 69 ± 7.0 years old. The average follow-up time was 15.3 ± 6.3 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months.…”
Section: General Datamentioning
confidence: 99%
“…However, this classi cation method was mostly applicable for unilateral puncture cases, because bilateral puncture injection of bone cement can often achieve a uniform distribution on both sides of the vertebral body, effectively avoiding the uneven stress caused by asymmetric distribution on the coronal plane. Many previous literatures have also con rmed that bilateral puncture does not signi cantly increase the risk of complications such as cement leakage and nerve injury as long as the puncture route is strictly followed [9,10]. Therefore, studying the distribution of bone cement in the sagittal plane on lateral radiographs may be more meaningful for the analysis of surgical e cacy.…”
Section: Discussionmentioning
confidence: 99%
“…There were 26 males and 111 females, with an average age of 69 ± 7.0 years old. The average follow-up time was 15.3 ± 6.3 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months.…”
mentioning
confidence: 99%
“…We have reviewed thoroughly literatures on several aspects on the relationship between surgical operation and residual pain. As many meta-analyses shown, PKP and PVP have no difference in pain improvement and function recovery [19,20]. 10 studies, from a meta-analysis with 16 studies [19], indicated no difference by comparing the pain improvement in PKP group and PVP group.…”
Section: Operation Related Factorsmentioning
confidence: 99%